Physiological responses according to rules changes during 3 vs. 3 small-sided games in youth soccer players: stop-ball vs. small-goals - Halouani, J.; Chtouro, H.; Dellal, A.; Chaouachi, A.; Chamari, K. (Journal of Sports Sciences, 2014)
Small-sided games (SSGs) are effective for soccer-specific aerobic endurance training. To date, no study has investigated the effect of stop-ball (SB-SSG) rule on the physiological responses to SSG. Therefore, the purpose of the present study was to examine the effects of SB-SSG vs. small-goals (SG-SSG) rules on physiological responses during a 3 vs. 3 SSG in young soccer players. Twelve male amateur young soccer players (age, 14.0 ± 0.7 years; body mass, 51.8 ± 8.0 kg; height, 164 ± 7 cm) randomly performed either SB-SSG or SG-SSG for 4 × 4 min separated by 2 min of recovery on a 20 × 15 m pitch. During the SB-SSG, participants were instructed to stop the ball with the soles of their boots in a 15 × 1 m surface behind the pitch bottom line; whereas during the SG-SSG, the participants were instructed to score to a mini-goal (i.e., 1 × 0.5 m). During each test session, the mean heart rate (HR), the post-SSG rating of perceived exertion (RPE) scores and blood lactate concentrations ([La-]) were recorded. Results showed that SB-SSG induced significantly higher mean HR (178 ± 3 vs. 174 ± 3 bpm; P < 0.05) and [La-] (4.66 ± 0.98 vs. 4.16 ± 1.02 mol /L; P < 0.05) than SG-SSG. However, there was no significant difference between SB-SSG and SG-SSG for the RPE scores. In conclusion, the present study demonstrates the effectiveness of SB-SSG in SSG training. Indeed, SB-SSG can influence the effort intensity in SSG (i.e., resulted in a higher intensity than SG-SSG). Therefore, coaches have the possibility to choose between SB-SSG and SG-SSG rules during training sessions according to their physical and technical objectives.